SISTEM IMUNITAS ALAMIAH DAN SISTEM IMUNITAS ADAPTIF - Dian Rahadianti; Herlinawati Herlinawati (Nusantara Hasana Berdikari, 2022)
The immune system is a collection of immune cells found in the blood and lymph fluid, in tissues and organs that work together to protect the body against attack by foreign substances, such as microbes (bacteria, fungi, and parasites), viruses, cancer cells, and toxins. The immune system is very complex, which can recognize and remember millions of different foreign substances. Immunity or resistance to infection is obtained from the activity and intact function of two closely related systems, namely the innate immune system and the acquired immune system (adaptive immune system). Exterior defenses, such as skin and mucous membranes, phagocytic leukocytes and serum proteins are elements of the innate immune system, which act nonspecifically against foreign substances or cells without having to recognize a specific identity. The adaptive immune system differs from the innate immune system, depending on the specific recognition by lymphocytes of foreign substances or cells. Understanding the functional interactions between the innate and adaptive immune systems is very important in future disease investigations and therapeutics.